Analysis of the Role of Attitude as a Mediating Variable in the Influence of Perceived Behavior Control, Subjective Norm, Religiosity and Trust on the Intention to Waqf Cash in the Clean Water Project at the Al-Quran Waqf Agency (BWA) - Eri Hartati Adi; Syafrizal Chan (Indonesian Journal of Business Analytics, 2025)
This study was conducted to analyze the role of attitude as a mediating variable in the influence of perceived behavioral control, subjective norm, religiosity, and trust on the intention to donate cash waqf for a clean water project at the Badan Wakaf Al-Qur'an (BWA. The sample measurement in this study uses Simple Random Sampling technique. The approach used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) 4.0. The results showed that Attitude, Perceived Behavioral Control, and Trust have a positive and significant effect on Intention to Endow money in Clean Water Projects. Subjective Norm and Religiosity do not have a significant direct effect on Intention. However, Attitude is proven to positively and significantly mediate the relationship between Subjective Norm, Religiosity, and Trust on Intention. This finding is expected to be a reference for waqf institutions and related parties in developing more effective communication strategies to encourage cash waqf participation, especially in supporting social projects such as clean water provision.